Effect of GEMARA (Monopoly Educational Game on Anemia) on Knowledge and Attitudes Toward Anemia Prevention Among Adolescents: A Health Belief Model Approach - Astuti, Yuli; Piping Asgiani; Dyah Artini (Poltekkes Kemenkes Semarang, 2025)
Adolescent anemia is a public health problem requiring special attention. It is commonly caused by iron deficiency related to rapid growth, menstrual blood loss, poor nutritional intake, unhealthy dietary habits, and inadequate knowledge about iron-rich foods and anemia prevention. Low adherence to iron supplementation and frequent consumption of foods that inhibit iron absorption further increase risk. Evidence shows that 16% of 50 adolescents experienced anemia. Effective educational strategies are needed to improve knowledge and attitudes. Health education becomes more attractive for adolescents when delivered using game-based learning, such as Monopoly educational media. To determine the effectiveness of GEMARA (Monopoly Educational Game on Anemia) using the Health Belief Model approach in improving adolescents’ knowledge and attitudes toward anemia prevention. A quasi-experimental one-group pretest–posttest design was conducted among 38 FORPIS PMI Yogyakarta members using total sampling. Intervention consisted of one session of health education using the GEMARA game with a peer-group approach. Data were collected with validated and reliable questionnaires adapted from previous studies (r > 0.361; Cronbach alpha > 0.70). Knowledge (numeric) and attitudes (ordinal) were analyzed using Wilcoxon Signed-Rank Test with SPSS 23. Knowledge improved significantly from fair (47.4%) and good (47.4%) to 76.3% good, with no poor category. Positive attitudes increased from 50% to 100%. Wilcoxon Signed-Rank Test indicated significant improvement (p=0.000; p=0.002). This improvement was driven by interactive learning that increased engagement and motivation. GEMARA is effective in improving adolescents’ knowledge and attitudes toward anemia prevention through the Health Belief Model.